MARRIAGE DISPENSATION AFTER LAW NO. 16 OF 2019: BETWEEN CHILD PROTECTION AND SOCIAL REALITY IN MONTONG GADING DISTRICT - Sahli, Muh. Sahli; Dewi, Rohani Inta (Politea : Jurnal Politik Islam, 2025)
This study aims to analyze the implementation of Law Number 16 of 2019 related to the marriage age limit, with a focus on the practice of marriage dispensation in Montong Gading District, East Lombok. Using a descriptive qualitative approach, data was obtained through interviews, observations, and documentation studies of KUA employees, parents, adolescents, and religious court judges. The results show that the practice of marriage dispensation is still widely used as a legal loophole to legalize child marriage, even though regulations have been tightened. The main factors driving the application for dispensation are social pressure, out-of-wedlock pregnancies, poverty, and low legal understanding. Meanwhile, the role of KUA as an administrative implementer is considered not optimal in prevention efforts, due to limited human resources and lack of collaboration with child protection institutions. The conclusion of the study emphasizes the importance of comprehensive reform, both in regulatory and implementive aspects, as well as the need for multidisciplinary involvement in every marriage dispensation process for the protection of children's rights. This research is expected to be a conceptual contribution to strengthening the role of local institutions in preventing early marriage